Decrease in Somatostatin-Positive Cell Density in the Amygdala of Females with Major Depression - Douillard-Guilloux, Gaelle (Depress Anxiety, 2016)
BACKGROUND: Somatostatin (SST) is a neuropeptide expressed in a subtype of gamma-aminobutyric acid (GABA) interneurons that target the dendrites of pyramidal neurons. We previously reported reduced levels of SST gene and protein expression in the postmortem amygdala of subjects with major depressive disorder (MDD). This reduction was specific to female subjects with MDD. METHODS: Here, we used in situ hybridization to examine the regional and cellular patterns of reductions in SST expression in a cohort of female MDD subjects with known SST deficits in the amygdala (N = 10/group). RESULTS: We report a significant reduction in the density of SST-labeled neurons in the lateral, basolateral, and basomedial nuclei of the amygdala of MDD subjects compared to controls. SST mRNA levels per neuron did not differ between MDD and control subjects in the lateral or basolateral nuclei, but were lower in the basomedial nucleus. There was no difference in cross-sectional density of total cells. CONCLUSIONS: In summary, we report an MDD-related reduction in the density of detectable SST-positive neurons across several nuclei in the amygdala, with a reduction in SST mRNA per cell restricted to the basomedial nucleus. In the absence of changes in total cell density, these results suggest the possibility of a change in SST cell phenotype rather than cell death in the amygdala of female MDD subjects.